Lipid Dysregulation in Gestational Diabetes Mellitus: Predicting Early Onset and Postpartum Outcomes - Sinha, Amita (Student's Journal of Health Research Africa, 2024)
Background: Gestational diabetes mellitus (GDM) poses significant health risks during pregnancy and beyond, necessitating research into predictive markers and management strategies. Lipid dysregulation, influenced by hormonal changes, plays a pivotal role in GDM pathophysiology. Objective: The review aims to synthesize current research on lipid dysregulation in GDM, focusing on its predictive value for early onset and postpartum outcomes, and to explore therapeutic implications. Review Summary: Lipid metabolism undergoes profound changes during pregnancy, further exacerbated in GDM. Elevated triglycerides, altered cholesterol levels, and disrupted lipid ratios are associated with increased GDM risk. Biomarkers like hs-CRP, SHBG, and miRNAs show promise for early GDM prediction. Postpartum lipidomic profiles reveal persisting dysregulation linked to future type 2 diabetes (T2DM) risk. Lactation may mitigate postpartum lipid changes and reduce T2DM risk. Clinical Policy and Development: The review underscores the importance of monitoring lipid profiles during pregnancy, employing early predictive biomarkers, and implementing personalized management strategies to mitigate GDM risks. Targeted interventions during pregnancy and postpartum lactation could aid in preventing or delaying T2DM onset. Future Implications: Further research into novel biomarkers, longitudinal lipid profiling, and tailored interventions is warranted to enhance GDM prediction and management, ultimately improving maternal and fetal health outcomes.